2021
DOI: 10.1038/s41598-021-84794-6
|View full text |Cite
|
Sign up to set email alerts
|

Padina boryana mediated green synthesis of crystalline palladium nanoparticles as potential nanodrug against multidrug resistant bacteria and cancer cells

Abstract: Green synthesized nanoparticles (NPs) have emerged as a new and promising alternative to overcome the drug resistance problem. Peculiar nano-specific features of palladium NPs (Pd-NPs) offer invaluable possibilities for clinical treatment. Due to the development of multi-drug resistance (MDR) in pathogenic bacteria and the prevalence of cancers, use of algae-mediated Pd-NPs could be a prospective substitute. Therefore, Pd-NPs were synthesized by a one-step, cost-effective, and environmentally friendly green me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(39 citation statements)
references
References 69 publications
4
35
0
Order By: Relevance
“…63 Based on the presented peaks, the presence of protein and polysaccharide in both tested materials (major peaks) suggested their contribution in the process of Ag ions reduction leading to the formation of J-AgNPs capped with biomolecules that prevent their aggregation. Similar findings were also noted [13,42]. The shift in peaks transmittance of FTIR signals for J-AgNPs concerning plant extracts might be due to probable interactions between functional groups (capping and reducing agents) and NPs or metal ions [43].…”
Section: Discussionsupporting
confidence: 76%
“…63 Based on the presented peaks, the presence of protein and polysaccharide in both tested materials (major peaks) suggested their contribution in the process of Ag ions reduction leading to the formation of J-AgNPs capped with biomolecules that prevent their aggregation. Similar findings were also noted [13,42]. The shift in peaks transmittance of FTIR signals for J-AgNPs concerning plant extracts might be due to probable interactions between functional groups (capping and reducing agents) and NPs or metal ions [43].…”
Section: Discussionsupporting
confidence: 76%
“…The biogenic materials in NPs formation provide capping agents (ie adsorption of molecules on the surface of NPs), which decides its final morphology and thus prevents the overgrowth of NPs. 80 , 81 Generally, the biosynthesis of AgNPs follows the reduction of Ag + ions to Ag 0 from electrons liberated mainly from the biogenic agent’s active biomolecules that finally cap the formed NPs. Currently, the color of AgNO 3 when mixed with each Phoma sp., Chaetomium globosum , and Chaetomium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent papers revealed that Pd nanoparticles obtained through a plantmediated biogenic approach are less toxic and biocompatible [33] and present important activity as an antioxidant, anticancer, antimicrobial and antiproliferative [9,10,12,[34][35][36][37][38][39][40][41][42][43][44], and can be used for environmental remediation [45]. Recent examples of the green synthesis of Pd nanoparticles mediated by plant extracts and their application as catalysts are shown in the Table 1.…”
Section: Plant Extractsmentioning
confidence: 99%